THE DIVERSITY OF BUTTERFLY IN AIR DINGIN LANDFILLS, BALAI GADANG, PADANG CITY - Leila Muhelni; Hendra Anwar (BERITA BIOLOGI, 2020)
The study of butterfly in the in Air Dingin Landfills needs to be carried out to find out what types of butterflies are in this area and how their diversity is, given the increasing area of Landfills that will change the surrounding environment into a place of rubbish heap. The study was conducted by implementing survey method with insect net. The collection of butterflies was carried out in 2 periods (2x6 = 12 days) in April-June 2019 during sunny weather from 09:00 – 12:00 of Western Indonesian Time. All butterflies were collected at ±5 m distance from the collector. The data was analysed to calculate abundance, relative abundance, frequency of the presence of butterfly, and determine diversity was conducted by using the Shannon-Wiener Index and Evenness index. The results obtained 5 families, 14 genera, 22 species, and 220 individuals consisting of 122 males and 98 females. The diversity index value obtained was 2.27 and categorised as the medium category it is mostly because, as assumed, the environmental conditions of the Air Dingin Landfills were still in good condition.